Trimethylammonium‐Derived Molecular Tweezers and Their Host–Guest Complexation Behaviours in Polar Media. Issue 12 (25th May 2016) - Gao, Zhao; Han, Yifei; Chen, Jiangjun; Wang, Xiao; Wang, Feng
Abstract: Trimethylammonium‐derived alkynylplatinum(II) terpyridine molecular tweezers have been designed and synthesized in this manuscript. They show moderate binding affinity towards the complementary organoplatinum guest in polar media, such as DMSO, methanol, and water, even though the guest itself is sparingly soluble in the latter two solvents. Responsive guest encapsulation/release from the cavity of molecular tweezers can be achieved by successive addition and removal of trifluoroacetic acid, accompanying with remarkable switching of the photophysical signals, which would benefit for the fabrication of intelligent supramolecular materials with tailored functionalities. Abstract : Introduction of a cationic trimethylammonium unit facilitates to enhance the solubility of the resulting alkynylplatinum(II) terpyridine molecular tweezers in polar medium, demonstrating moderate binding affinity, unique photophysical behaviors, and pH‐responsiveness towards the complementary guest (see figure).